Frontline heroes - Hudd, Emily (Core library guide to Covid-19, 2021)
Health-care workers were on the front lines during the COVID-19 pandemic, saving lives and searching for effective treatments. Other workers, such as grocery clerks and delivery people, also found themselves on the front lines as the rest of society stayed home as much as possible to slow the disease's spread. Frontline Heroes examines these and other people who faced danger as they continued working to keep the rest of society safe.